Political Party Criminal Liability Models in Corruption Cases: A Comparative Analysis between Indonesia and France - Ali, Hilmy Faidulloh; Djatmika, Prija; Yuliati, Yuliati; Istiqomah , Milda (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Political parties occupy a central institutional position in democratic systems but are recurrently associated with corruption that benefits organisations collectively rather than solely individual actors. Specific Background Indonesia’s National Criminal Code recognises corporations as subjects of criminal liability, thereby opening doctrinal space for prosecuting political parties, while France has long applied legal person liability under Article 121-2 of the Code pénal, supported by strict political finance supervision. Knowledge Gap Despite normative recognition in Indonesia, political parties are rarely treated as corporate offenders in corruption cases, creating a gap between legal construction and enforcement practice. Aims This study analyses the construction of political party criminal liability under Indonesia’s National Criminal Code, examines the French model, and compares both systems to identify a more coherent liability framework. Results The findings show that Indonesia provides a broad normative basis for treating political parties as corporate criminal subjects but lacks clear implementing mechanisms, whereas France demonstrates a consolidated and operational model combining criminal liability with institutional financial oversight. Novelty This study offers a focused comparative analysis positioning political parties explicitly as corporate offenders within corruption law, highlighting structural rather than individual accountability. Implications The analysis underscores the need for clearer legislative articulation and strengthened institutional design in Indonesia to ensure that political parties benefiting from corruption can be held criminally accountable, drawing lessons from the French experience. Highlights: Indonesia’s criminal law framework recognises organisational responsibility but rarely extends prosecution beyond individual perpetrators. France applies legal person responsibility to political organisations through clear doctrine and dedicated financial supervision. Comparative analysis reveals institutional design as a decisive factor in enforcing accountability for corruption. Keywords: Corporate Criminal Liability, Political Parties, Corruption Offences, Indonesia, France